0291 Recovery Sleep Alleviates Mood Disturbance Following Chronic Sleep Restriction, Albeit Transiently and in a Dose-Dependent Manner. (27th May 2020) - Mange, A; Jones, C W; Kaizi-Lutu, M; Basner, M; Dinges, D F
Abstract: Introduction: Fatigue is one contributor to mood disturbance observed following sleep restriction; however, the contribution of other factors remains unclear. This study examined contributions to mood disturbance resulting from sleep restriction beyond that of fatigue, evaluated the benefit of recovery sleep, and assessed whether recovery sleep buffered the re-emergence of mood disturbance upon re-exposure to sleep restriction. Methods: N=223 healthy participants (48% female; n=108) approximately 30-years-old (SD=6.89, range=22–45 years) completed two baseline nights of 8h time in bed (TIB), followed by five nights of 4h TIB, and were then then randomized to one of 7 sleep recovery opportunities (i.e., 0, 2, 4, 6, 8, 10, or 12 hours TIB). Following the sleep period, a subset of participants (n=72) were re-exposed to five consecutive nights of 4h TIB. The profile of mood states (POMS) was completed every 2h during wakefulness and daily averages were calculated. The POMS total mood disturbance (TMD) score without the fatigue subscale (i.e., mood disturbance = TMD - fatigue) was the primary outcome to isolate changes in mood disturbance beyond fatigue. Individual growth curve models were applied to the trajectory of mood disturbance. General linear models were used to evaluate the dose-response function of mood disturbance after recovery sleep. Results: Mood disturbance (absent the POMS fatigue scale) increased with each day of sleep restriction (β=1.550 per day; P<0.0001), and decreased with longer recovery sleep durations in a dose-dependent manner (β=-1.614 for every 2h increase; P<0.0001). The benefits of recovery sleep were abated by the second night of 4h sleep during re-exposure, where mood disturbance was slightly higher than that observed before recovery, but this difference was not statistically significant (β=0.046; P=0.85). Conclusion: The study findings suggest that fatigue is not the only contributor to mood disturbance following sleep restriction. Recovery sleep attenuates mood disturbance in a dose-dependent manner, albeit transiently. Candidate pathways linking sleep restriction and mood include the immune system and the dynamics of sleep physiology. Support: This work was funded by National Institute of Health NIH R01NR004281 and National Space and Biomedical Research Institute NSRBI NCC 5–98.